A precise time-integration linear vehicle-bridge interaction method and dynamic sensitivity analysis. (October 2021) - Shao, Yuefeng; Brownjohn, J.M.W.; Miao, Changqing; Wang, Miaomin
Abstract: A linear dynamic vehicle-bridge interaction method is proposed in this paper. This VBI system can be easily simulated by a step-by-step solution technique based on precise time-integration method following discretization of the bridge and modal analysis of the finite element model. By selecting the target structural mode with high modal participation in finite element modal analysis, the huge computational overhead caused by the multi-degrees of freedom of large structures in the dynamic response analysis can be effectively reduced. In this integration process, the characteristics of precise time-integration method can be used to ensure the stability and accuracy of the iterative calculation when selecting a relatively large time integration step. This provides the possibility to investigate the VBI problem in large-scale bridges. In this work, a half-vehicle model case and an experiment on full-vehicle model are used to verify the application of the algorithm. Then the dynamic sensitivity of a beam is analyzed based on the dynamic amplification factor.